The Effect of Wattpad Application on Narrative Text Reading Comprehension of the Eighth Graders at SMPN 3 Banyuwangi - Siti Yohanita Fitriani; Wageyono; Lailatul Farihah; Indah Aprilia Puspita Sari (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2026)
The purpose of this study was to determine the significant effect of using the Wattpad application on students' reading comprehension. The method used in this research is quantitative with a one group pretest-posttest research design. The respondents of this study were 8th grade students at SMPN 3 Banyuwangi. In this study, researcher used one class as a sample. The subjects in this study were students of class VIIIB consisting of 32 students. The researcher conducted this study for two meetings: the first day for pre-test and treatment and the last day for treatment and post-test. The researcher used a test as an instrument. After the data was obtained, the researcher calculated the data using the Wilcoxon test. Based on the calculation results, the mean value of the pretest was 64.70 and the mean value of the posttest was 81.5. To verify the hypothesis statistics, the Wilcoxon test results were compared with the 5% significance level. From the results, it was found that the Wilcoxon test result was smaller than 0.05. Thus, it can be concluded that there is an effect of using wattpad application on reading comprehension of grade VIII students at SMPN 3 Banyuwangi. The findings of this study imply that the use of the Wattpad application can be an effective digital learning medium to enhance students’ reading comprehension, particularly in understanding narrative texts. It also indicates that integrating engaging and interactive platforms like Wattpad can increase students’ motivation and participation in reading activities.